Potensi ekstrak tanaman kirinyuh (Chromolaena odorata L.) Sebagai insektisida nabati untuk pengendalian hama larva kumbang tanduk (Oryctes rhinoceros L.) - Arbit, Muliani; Zaenal Mutaqin; Nova Ardianti (Fakultas Pertanian Universitas Majalengka, 2024)
This study aimed to utilize kirinyuh (Chromolaena odorata L.) leaf extract (KLE) as a plant-based insecticide for pest control in Oryctes rhinoceros L. The research was conducted for 4 months, from April to July 2023, at the Pontianak State Polytechnic Plantation Plant Science Laboratory. Complete Randomized Design (CRD) with five treatments and 5 Replications. The treatment are 0% (without KLE, as a control); 30% (30 ml KLE + 100 ml aquades); 40% (40 ml KLE + 100 ml aquades); 50% (50 ml KLE + 100 ml aquades); and 60% (60 ml KLE + 100 ml aquades). Each treatment was repeated 5 times for 25 treatment units, with each treatment unit storing as many as ten larvae of O rhinoceros L. The variables observed were the symptoms of death and the mortality rate of O rhinoceros L. The data obtained were analyzed with ANOVA, and continued by analyzing the Smallest Real Difference test with α = 95%. The results showed that all O rhinoceros L. larvae treated with KLE experienced death symptoms with colour changes from brown to blackish. The highest mortality rate occurred in the treatment of 30% of KLE, with the fastest time of death being 22 days. It can be concluded that KLE has flavonoid phytochemical compounds, alkaloids, tannins, and saponins. Kirinyuh leaf extract significantly affected the mortality of larvae III Oryctes rhinoceros L. with Lethal Concentrate (LC50) of 23.85% concentration and Lethal Time (LT50) of 22.86 days. The concentration between kirinyuh leaf extract treatments had no significant effect on the mortality of Oryctes rhinoceros L larvae.